Biometry of the crystalline lens in early-onset diabetes. Issue 11 (November 1990) - Sparrow, J M; Bron, A J; Brown, N A; Neil, H A
Abstract : Lenticular biometry on non-cataractous lenses has been studied by means of Scheimpflug photography and digital image analysis in 153 patients with early-onset insulin-dependent diabetes and 153 non-diabetic controls. Anteroposterior axial lens thickness, cortical thickness, nuclear thickness, anterior and posterior lenticular curvatures, and anterior chamber depth were assessed. Highly significant differences between the lenses of the diabetic subjects and non-diabetic controls were found. After the effect of age had been accounted for within the diabetic subgroup, diabetic duration was found to be a highly significant determinant of lens dimensions, such that age-related dimensional changes for various biometric parameters were accelerated by between 52% and 121% after the onset of diabetes. Because the diabetic duration of the early-onset diabetic subjects studied in this work was accurately known, this report is the first in which a precise assessment of the effect of 'true' diabetic duration on lens biometry has been possible.